Pendidikan dan Pelatihan Dasar Penelusuran Bahan Ajar dari Internet bagi Guru-guru SD di Baki Sukoharjo - Maria Atik Sunarti Ekowati; Sri Wening; Kristyana Dananti (CV. ALIM'SPUBLISHING, 2023)
The internet has a broad impact in the world of education, changing traditional ways of education to modern ways. The presence of the internet can overcome and change the limitations of distance, learning resources and information sources, so that students can be active in understanding the subjects taught by teachers to students. Utilization of the internet network as a source of basic education and training. Searching for teaching materials and sources of information in learning can be implemented through browsing, resourcing, searching, consulting and communicating. Utilizing the internet by utilizing the web in learning can be done through web courses, web centric courses, and web enhanced courses. The use of the internet must be done with full awareness so that the presence of the internet can truly support learning activities, especially for elementary school teachers in the Baki sub-district, Sukoharjo district. Internet misuse can have a negative impact on learning due to inaccuracies in the data or information presented. Therefore, internet users must be selective in choosing learning sources and information presented by the internet.